Toward Unveiling the Mechanisms for Transcriptional Regulation of Proline Biosynthesis in the Plant Cell Response to Biotic and Abiotic Stress Conditions - Zarattini, Marco; Forlani, Giuseppe (Frontiers in Plant Science, 2017)
Proline accumulation occurs in plants following the exposure to a wide array of stress conditions, as well as during numerous physiological and adaptive processes. Increasing evidence also supports the involvement of proline metabolism in the plant response to pathogen attack. This requires that the biosynthetic pathway is triggered by components of numerous and different signal transduction chains. Indeed, several reports recently described activation of genes coding for enzymes of the glutamate pathway by transcription factors belonging to various families. Here we summarize some of these findings with special emphasis on rice, and show the occurrence of a plethora of putative transcription factor binding sites in the promoter of such genes.